Gauging Radical Stabilization with Carbenes - Breitwieser, Kevin; Bahmann, Hilke; Weiss, Robert; Munz, Dominik (Angewandte Chemie International Edition, 2022)
Carbenes, including N-heterocyclic carbene (NHC) ligands, are used extensively to stabilize open-shell transition metal complexes and organic radicals. Yet, it remains unknown, which carbene stabilizes a radical well and, thus, how to design radical-stabilizing C-donor ligands. With the large variety of C-donor ligands experimentally investigated and their electronic properties established, we report herein their radical-stabilizing effect. We show that radical stabilization can be understood by a captodative frontier orbital description involving pi-donation to- and pi-donation from the carbenes. This picture sheds a new perspective on NHC chemistry, where pi-donor effects usually are assumed to be negligible. Further, it allows for the intuitive prediction of the thermodynamic stability of covalent radicals of main group- and transition metal carbene complexes, and the quantification of redox non-innocence.
CRIS-Team WoS Importer:2022-08-19